Manifestasi Modal Sosial: Pengaruh Keaktifan Berorganisasi dengan Perluasan Jejaring Bisnis pada BPD HIPMI Jawa Tengah - Belia Mulyaningtyas; Firda Nisafera Ulfa (Jurnal Salingka Nagari, 2025)
This study examines the influence of organizational engagement on business network expansion among young entrepreneurs in the BPD HIPMI Central Java. Utilizing a quantitative approach, data from 133 active members selected via purposive sampling were processed using simple linear regression analysis. Preliminary evaluations confirmed that all research instruments achieved high validity and reliability. Furthermore, classical assumption tests verified that the data followed a normal distribution, remaining free from multicollinearity and heteroscedasticity. Statistical results yielded the regression equation Y=3.746+0.705X, with a t-value of 23.450 significantly exceeding the t-table of 1.65639 (p<0.05). These findings demonstrate a robust positive correlation, proving that active participation within an organization substantially enhances business networking capabilities. An Adjusted R Square of 0.808 indicates that organizational involvement accounts for 80.8% of the variance in network development, while external factors influence the remaining 19.2%. Ultimately, this research underscores that intensive organizational commitment serves as a primary catalyst for young entrepreneurs to cultivate productive and sustainable business ecosystems within HIPMI Central Java.